2018
DOI: 10.1159/000493824
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S Inhibits Autophagy in Unilateral Ureteral Obstruction Mouse Renal Tubule Cells by Regulating the ROS-AMPK Signaling Pathway

Abstract: Background/Aims: The induction of excessive autophagy by increased levels of oxidative stress is one of the main mechanisms underlying unilateral ureteral obstruction (UUO)-induced vascular endothelial cell dysfunction. Hydrogen sulfide (H2S) has been shown to have an anti-oxidative effect, but its mode of action on excessive autophagy in vascular endothelial cells is unclear. Methods: Surgery was used to induce UUO in male C57BL/6 mice as an in vivo model. Human renal epithelial cells (HK-2) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In recent years, it has been found that autophagy is closely related to the protective effect of H 2 S. Pretreatment with NaHS could alleviate acute myocardial ischemia injury by suppressing autophagy under oxidative stress, significantly reducing brain damage and preserving the blood-brain barrier integrity after traumatic brain injury by inhibiting autophagy via activation of the PI3K/Akt/mTOR signaling pathway and mitigating acrylonitrile-induced decrease of cell viability through influencing autophagy (Bai et al, 2018; Xu et al, 2018; Yang et al, 2018). Exogenous H 2 S also might protect mouse kidney against unilateral ureteral obstruction by suppressing ROS-AMPK-mediated autophagy, ameliorating blood-spinal cord barrier disruption and improving functional recovery by suppressing endoplasmic reticulum stress-mediated autophagy and inducing the apoptosis of hepatocellular carcinoma cells through promoting autophagy via the PI3K/AKT/mTOR signaling pathway (Chen et al, 2018a,b; Wang et al, 2017, 2018). Autophagy has also been reported to be closely related to NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been found that autophagy is closely related to the protective effect of H 2 S. Pretreatment with NaHS could alleviate acute myocardial ischemia injury by suppressing autophagy under oxidative stress, significantly reducing brain damage and preserving the blood-brain barrier integrity after traumatic brain injury by inhibiting autophagy via activation of the PI3K/Akt/mTOR signaling pathway and mitigating acrylonitrile-induced decrease of cell viability through influencing autophagy (Bai et al, 2018; Xu et al, 2018; Yang et al, 2018). Exogenous H 2 S also might protect mouse kidney against unilateral ureteral obstruction by suppressing ROS-AMPK-mediated autophagy, ameliorating blood-spinal cord barrier disruption and improving functional recovery by suppressing endoplasmic reticulum stress-mediated autophagy and inducing the apoptosis of hepatocellular carcinoma cells through promoting autophagy via the PI3K/AKT/mTOR signaling pathway (Chen et al, 2018a,b; Wang et al, 2017, 2018). Autophagy has also been reported to be closely related to NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H 2 S can significantly improve myocardial inflammatory injury induced by ischemia, reduce the release of inflammatory mediators, inhibit the production of inflammatory mediators in primary myocardial cells of rats induced by lipopolysaccharide (LPS) and alleviate inflammatory injury of gastric mucosal cells induced by ischemia-reperfusion (Sodha et al, 2009; Elrod et al, 2007; Toldo et al, 2014; Guo et al, 2014). Exogenous H 2 S also inhibits oxidative stress response and weakens LPS-induced acute renal inflammatory injury (Chen et al, 2018a,b), inhibits the activation of inflammasome by sodium urate crystallization and reduces the release of proinflammatory factors (Castelblanco et al, 2018). At present, the relationship between H 2 S and NLRP3 inflammasome has gradually become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Change in intracellular ROS levels were by measuring the oxidative conversion of cell permeable 2′,7′-dichlorofluorescein diacetate (DCFH-DA, Sigma) to fluorospectro-photometer ( Chen et al, 2018 ). Cells were plated in 6 cm dish (1 × 10 6 cells/well) and allowed to attach overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is induced in response to diverse stimuli of ALI, including bacterial infection, lipopolysaccharide (LPS) exposure, sepsis, trauma, hyperoxia, pharmaceutical exposure, and mechanical ventilation [ 241 ]. One of the major inducers of autophagy in ALI is increased oxidative stress, which has been shown to promote autophagy in a number of lung cell lines and animal models of lung injury [ [242] , [243] , [244] ]. However, the role of autophagy in ALI still remains controversial ( Fig.…”
Section: Autophagy and Ros In Pulmonary Diseasesmentioning
confidence: 99%